Revisiting the possible creation of the quantum - Voronov, Vladimir Kirillivich (Discoveries in Agriculture and Food Sciences, 2015)
In the present work, a previously reported idea has been further developed. The idea is based on the earlier proposed visualization of Shor’s states. Therefore, the paper deals with some ideas of quantum physics, which constitute the basis of a set of the quantum objects, employed as q–bits, their possible structure and composition being disclosed. Quantum limit is implemented in cases where the characteristic of the quantum length defined by the de Broglie wavelength is equal to or lower than the physical size of the object. It is this condition should somehow be reflected in the composition and structure of the kantovyh Islands, which should serve as qubits. In other words, in the technological sense of dimensional quantum effects in this particular case, it is necessary to understand both the need for such facilities in the process of materializing States Shore, which would match the size (dimensions) of individual quantum islet and a critical length, describing it (the island) structure and (or) property. Also, necessary operations, performance of which at the technological level will allow for electronic unit to organize quantum computation procedure, are analyzed. It is shown that if operations with matrixes are used, the process of quantum computation can take reasonable amount of time.